The effects of combined self-talk, imagery and video-modelling interventions on anaerobic performance, heart rate response and self-efficacy - Sato Nursahaniza, Azizuddin Khan Thariq Khan, Jusoh Normah (Universiti Pendidikan Sultan Idris, 2017)
The effects of combined self-talk, imagery and video-modelling interventions on anaerobic performance, heart rate response and self-efficacy by Sato Nursahaniza, Azizuddin Khan Thariq Khan, Jusoh Normah,